View of the Someshwar Mahadev temple complex - Temples of India Project Team (Jio Institute, 2024)
The Someshwar Mahadeva Temple is a panchayatana (main shrine with four subsidiary shrines) temple. It is raised on a high plinth. The central shrine is dedicated to Shiva. It is surrounded by four minor shrines in four corners of the plinth, of which only two shrines are extant. As far as the two other minor shrines are concerned, only the remains of the plinth have been preserved. The entire complex can be approached via a flight of steps. At one point in time, a torana (arched gateway) might have stood at the entranceway, as indicated by the remains of the two pillar bases. In addition, there is also another fully preserved pillar to the right of the central shrine.